Black Freedom in the Age of Slavery : Race, Status, and Identity in the Urban Americas - Marks, John Garrison (Carolina lowcountry and the Atlantic world., 2020)
"Black Freedom in the Age of Slavery examines the intersection of race and identity among free people of African descent in the urban Americas during the late eighteenth and early nineteenth centuries. The manuscript uses the Atlantic port cities of Charleston and Cartagena as illustrative case studies in constructing a broad comparative framework that examines the experiences of free people of African descent in both the English and the Iberian Atlantic World. It argues that the efforts of free people of color throughout the urban Americas fought to improve their immediate social and material conditions, in the process challenging the logic of white racial hierarchies while also dividing communities of color along lines of class, color, and ancestry. The manuscript explores how free people of color across the urban Americas used labor, institutional ties, religious rites, and engagement with the intellectual and cultural currents of the broader Caribbean and Atlantic worlds to achieve social distinction and economic stability for themselves, their families, and their communities. As free people of African descent claimed rights and privileges not typically available to African-descended people, they revealed the complex relationship between race and rights in the early modern world. And yet, these efforts also defied any shared experience of black freedom, as class and complexion critically opened possibilities for some free people of African descent while closing them off for others. Indeed, as some free people of color at times directly confronted white authorities' formal and informal codes of racial supremacy, others accommodated them as necessary in order to improve their daily lives. By exploring the lives and communities of free people of color from across the African Americas, this manuscript reveals that efforts of free people of African descent to redefine their place in the socio-racial hierarchies of American society, even in very limited ways, made possible the more explicit contests of race and rights that would unfold throughout the hemisphere in the century following the abolition of slavery"--